An Irish national vegetation classification system for aquatic river macrophytes. Issue 2 (6th February 2018) - Weekes, Lynda; Kącki, Zygmunt; FitzPatrick, Úna; Kelly, Fiona; Matson, Ronan; Kelly‐Quinn, Mary
Abstract: Aim: To construct a classification system for Irish aquatic river vegetation that is directly comparable to European aquatic vegetation classification units. Location: A total of 2, 415 river vegetation plots with a wide geographic distribution across both the Republic and Northern Ireland. Methods: The plots were recorded from a range of river types from upland streams to wadeable lowland rivers. A total of 1, 613 plots were classified using supervised K‐means clustering through the programme JUICE. The Phi co‐efficient for presence/absence data was used to measure fidelity of the vegetation communities. Results: The vegetation communities could be initially sub‐divided in to four main categories: (1) bryophyte‐dominated aquatic vegetation, (2) bryophyte‐dominated marginal vegetation, (3) vascular plant‐dominated aquatic vegetation and (4) vascular plant‐dominated marginal/emergent vegetation. Within these four categories the vegetation was classified into seven classes, 18 alliances and 30 associations. Descriptions are given for each including variants and sub‐associations if found at association level. Conclusions: There is a rich diversity of bryophyte communities within Irish rivers and they are an integral part of the river network, whereas there was less diversity among vascular plant communities. The distinction between some communities was not as sharp as expected for a variety of reasons discussed in this paper, nevertheless, a working classification system was constructed. Abstract : The Leannan River, Rathmelton, County Donegal, Ireland.